Efecto del manejo en edad de reproductoras y temperatura de incubación sobre ventana de nacimiento y calidad del pollito BB - Cedeño Rivera, Oscar Adolfo (2022)
The effect of managing breeder age and incubation temperature on hatch window and chick quality was evaluated under a completely randomized design (DCA), made up of four treatments: 30-week-old breeder eggs incubated at 37.2ºC (T1), 34 weeks at 37.5ºC (T2), 38 weeks at 38ºC (T3) and 42 weeks at 37.8ºC (T4). The evaluated variables: birth window, weight gain, yolk sac absorption, organ weight; visceral package and microbiological quality due to the presence of bacteria and fungi. The results in the hatching window show significant differences (p<0.05) between the treatments with more chicks hatched for T3, T1 obtained the lowest weight gain 59.8 (gr) compared to 71.6 (gr) T2 and T4 and 72.9 (gr) T3; regarding the absorption of the yolk sac there are significant differences (p<0.05) between T1 64.90% compared to the other treatments with 90% and 92%, in the microbiological analysis the presence of E coli was found for T1 in all the samples; while T3 and T4 only one case, with a negative result for salmonella, do not show the presence of aspergillus and penicillium in any of the treatments. It is concluded that the chicks from younger breeders incubated at lower temperatures take longer to hatch, the weight gain per week was better for T3 chicks, the T1 chicks presented lower percentages of yolk sac absorption and had presence of E. Coli, no presence of fungi was found.